Extension of the sine-Gordon expansion scheme and parametric effect analysis for higher-dimensional nonlinear evolution equations - Chu, Yu-Ming; Fahim, Md Rezwan Ahamed; Kundu, Purobi Rani; Islam, Md Ekramul; Akbar, M. Ali; İnç, Mustafa (Elsevier, 2021)
Different wave solutions assist to interpret phenomena in different aspects of optics, physics, plasma physics, engineering, and other related subjects. The higher dimensional generalized Boussinesq equation (gBE) and the Klein-Gordon (KG) equation have remarkable applications in the field of quantum mechanics, recession flow analysis, fluid mechanics etc. In this article, the soliton solutions of the higherdimensional nonlinear evolution equations (NLEEs) have been extracted through extending the sineGordon expansion method and we analyze the effect of the associated parameters and the phenomena establishing the lump, kink, rogue, bright-dark, spiked, periodic wave, anti-bell wave, singular soliton etc. Formerly, the sine-Gordon expansion (sGE) method was used only to search for lower-dimensional NLEEs. In order to illustrate the latency, we have portrayed diagrams for different values of parameters and it is noteworthy that the properties of the features change as the parameters change. (C) 2021 The Author(s). Published by Elsevier B.V. on behalf of King Saud University.
Keywords: sGEM; gBE; KGE; Soliton solutions